Revitalisasi Amaliah Nahdlatul Ulama (NU) dalam Menangkal Faham Radikalisme di Madrasah Aliyah - Zulfa Fiqria; Zaenal Arifin (Indonesian Journal of Islamic Education Studies (IJIES), 2021)
The spread of radicalism in education requires students to fortify and strengthen their beliefs to not fall into radicalism. The researcher aims to discover the revitalization of NU’s practice in countering radicalism in schools. In this study, the type of field research is descriptive analysis. This study resulted in research findings, namely the implementation of NU’s Islamic tradition in the form of grave pilgrimage of Walisanga and Asmaul Husna reading, as well as a form of revitalization in countering radicalism through NU’s Islamic tradition practice for strengthening Aswaja’s theology.